Probability of falling and fear of falling after balance workshop in elderly practioners of physical activity - Anjos, Fabiana Ribeiro dos; Gonçalves, Andréa Kruger; Griebler, Eliane Mattana; Hauser, Eduardo; Fraga, Rayane Brum de; Benin, Lilian; Bós, Ângelo José Gonçalves; Teixeira, Adriane Ribeiro (Journal of Health Care, 2015)
Introduction: Falls are frequent events in the elderly, causing restriction of social participation, especially by fear of further falls. Objective: To assess the risk of falls and the fear of falling in elderly practitioners of physical activity before and after balance workshop. Materials and Methods: Subjects were evaluated before and after the workshop, which was developed for six months, twice a week. The Functional Reach Test (FES-I) was used for the evaluation of the probability of falling. The fear of falling was assessed using the Falls Eficacy Scales - International (FES-I). Results: We evaluated 17 elderly of both genders, with a mean age of 75.5±8.5 years. The mean values pre and post-workshop were, respectively, 34.2±6.5 and 36±4cm, in the Functional Reach Test (p=0.09) and 22.8±4.8 points and 23.5±4.7 points in FES-I (p=0.19). Conclusion: It was found that the likelihood of falls and fear of falling were not significantly modified with the workshop, probably because the elderly were practitioners of guided physical activity.